SPESIFICITY OF BI – CONTAINING HTSC COMPOUNDS SYNTHESIS: UDC 546.312.62. (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Comparative analysis of literature data of synthesis of oxide superconducting materials, particularly Bi-containing cuprates, havebeen made. It was shown that depending of HTSC product and field of its using different ways of synthesis can be appropriate.
Keywords: -